Prevention of the Stigma of Mental Disorders in the Community - Retno Puji Astuti; Antonia Rensiana Reong; Fakhrun Nisa' Fiddaroini; M. Elyas Arif Budiman (Universitas Airlangga, 2019)
The stigma felt towards clients with mental disorders is still negative in community. Health education programs are run by health workers in order to reduce the stigma for clients with mental disorders in the community. These programs have been widely implemented but there has been a low impact on the community thus far. The aim of this study was to gain an insight into the stigma focused on clients with mental disorders in the community. The databases used were SCOPUS, ProQuest, SAGE and Science Direct in order to identify potential articles. The articles were limited to being published in a range of 5 years from 2013 to 2018. The keywords used in the literature review were “stigma” AND “community” AND “mental disorder”. This study reports on the latest experience of stigma in relation to clients with mental disorders. The stigma is given from the community to the client with a mental disorder at 4 levels, namely labeling, stereotype, exclusion and discrimination. This makes the social life of the clients disturbed. Stigma and the prevention of it must therefore be further developed in the community. The results of this systematic review should be considered to reduce and prevent stigma in clients with mental disorders.